AMR DAN NAHYI DALAM AL-QURAN (Analisis Pragmatis Tindak Tutur Imperatif dab Prohibitatif dalam Al-Quran Surat An-Nisa) - Nurohman, Tsabit (2015)
This study departs from the phenomenon of verbal as well as the importance of understanding the meaning and function Amr and nahyi because it is often used in a variety of contexts both on the language of religious texts as well as in the daily life of Muslims. This study aims to identify and understand the element of Imperative Speech Acts and Pragmatics Prohibitatif in EMQ. The method used is descriptive literature through the instrument in the form of documents. This research has found a number of sentences Amr and nahyi in EMQ. Speech Acts form in Surah An Nisa consist Follow dai said Direct, indirect speech acts, acts Tak said Literal and Literal and follow Said Jump and Tak Literal. In addition there is also the meaning of speech acts such locutions commands and prohibitions, illocutionary speech acts such as commands and prohibitions of meaning other than as a threat, instructions, warnings, glorify, proscribe, advocate and obliging. As for the speech act Amr Perlokusi good and meaningful nahyi Hope. ---------- Penelitian ini berangkat dari fenomena verbalisme serta pentingnya memahami makna dan fungsi Amr dan Nahyi karena seringkali digunakan dalam berbagai konteks berbahasa baik pada teks-teks keagamaan maupun dalam kehidupan sehari-hari umat muslim. Penelitian ini bertujuan untuk mengetahui dan memahami Unsur Pragmatik Tindak Tutur Imperatif dan Prohibitatif dalam Q.S An Nisa. Adapun metode yang digunakan ialah metode deskriptif Kepustakaan melalui instrument berupa dokumen. Dari penelitian ini telah ditemukan sejumlah kalimat Amr dan Nahyi dalam Q.S An Nisa. Bentuk Tindak Tutur dalam Surat An nisa terdiri dai Tindak tutur Langsung, Tindak tutur tidak langsung, Tindak tutur Literal dan Tak Literal serta tindak Tutur Langsung dan Tak Literal. Selain itu terdapat juga tindak tutur Lokusi berupa makna perintah dan larangan, tindak tutur Ilokusi berupa makna selain perintah dan larangan seperti ancaman, petunjuk, peringatan, memuliakan, mengharamkan, menganjurkan dan mewajibkan. Sedangkan untuk tindak tutur Perlokusi baik Amr dan Nahyi bermakna Pengharapan.